Infeksi Subletal Bacillus thuringiensis pada Helicoverpa armigera: Mungkinkah Menyebabkan Resurgensi? - Tjandra Anggraeni; Ramadhani Eka Putra; Intan Ahmad (Jurnal Perlindungan Tanaman Indonesia, 2001)
Research on the effect of B. thuringiensis sublethal infection to the chance of H. armigera to resurgence has been conducted. Third instar insects were used and the concentration applied were 0 ppm, 150 ppm, 300 ppm, 450 ppm and 600 ppm. The result showed that along with the increase of B. thuringiensis infection, the number and the viability of the eggs production declined. In addition, the weight difference between the 3rd and the 4th instar became higher however between the 4th and the 5th became lower, moreover, the weight of female imago decreased, the life longevity of male and female imago were shorter and longer, respectively, along with the increase of B. thuringiensis infection. The possibility for resurgence will be discussed.